A Review of the Possibility Integrating the Solar System into the Libyan Railway Transportation - Ibrahim Imbayah; Abdussalam Ali Ahmed; Abdulgader Alsharif; Mohamed Mohamed Khaleel; Ahmed Alarga (African Journal of Advanced Pure and Applied Sciences, 2023)
This study of the possibility of integrating clean energy into the Libyan railway transport system using the integration of photovoltaic cells provides the potential for electric power, whether in the development of transit trade or the production of renewable electric energy near the points of electricity consumption. In Libya, for example, by integrating photovoltaic cells at stations, up to 100% of the electricity demand at railway stations can be covered, and the surplus will support the public electricity grid. Political support (for buildings in integrated photovoltaic plants) BSIPV will contribute to the development of transit trade in Libya. This study suggests the exploitation of solar systems in the railway transport system and the distribution of renewable energy sources along the railway lines in Libya, which is a link between Africa and Europe. And I will propose innovative ideas that achieve integration between railway transportation and solar energy.